2019
DOI: 10.1007/s00784-019-02858-4
|View full text |Cite
|
Sign up to set email alerts
|

Observations, knowledge, and attitude towards treatment options in patients with dry mouth: a survey among German dentists

Abstract: Objectives The aim of this study was to investigate the attitude, observations, and knowledge of German dentists regarding the management of dry mouth. Materials and methods A questionnaire including queries about attitudes, observations, and treatment options in patients with dry mouth was developed and sent to all 1251 dentist members of a regional German dental association. Results An overall total of 284 returned questionnaires were included in the analyses, which relates to a response rate of 22.7%. Denti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 16 publications
3
4
0
Order By: Relevance
“…This is the first study to assess Croatian dentists’ subjective ratings of specific CR factors in making a caries treatment plan in their adult patients, and about the percentage of Croatian practitioners performing CRA. Unfortunately, the response rate to the questionnaire was rather low (17.1%), similar to Mayer et al study ( 12 ). This might partially be due to the use of an internet based questionnaire since the response rate in a similar postal questionnaire survey undertaken in France in 2015 was considerably higher (34.7%), ( 9 ).…”
Section: Discussionsupporting
confidence: 83%
“…This is the first study to assess Croatian dentists’ subjective ratings of specific CR factors in making a caries treatment plan in their adult patients, and about the percentage of Croatian practitioners performing CRA. Unfortunately, the response rate to the questionnaire was rather low (17.1%), similar to Mayer et al study ( 12 ). This might partially be due to the use of an internet based questionnaire since the response rate in a similar postal questionnaire survey undertaken in France in 2015 was considerably higher (34.7%), ( 9 ).…”
Section: Discussionsupporting
confidence: 83%
“…The data collection was performed from Sep 2020 to Dec 2020. A questionnaire was prepared for the study on the basis of previous similar studies, [5][6][7][8] which was later modified after consultations with three Prosthodontist colleagues.…”
Section: Methodsmentioning
confidence: 99%
“…Exploring how dentists and dental hygienists in general dental care address oral dryness is important, but there are few studies on this subject. According to a German study, dentists were aware of the psychological and clinical consequences of dry mouth but were unsure of how to identify and treat the affected patients [ 22 ]. Similarly, another study showed a high awareness of the condition but uncertainty on how to manage and treat individuals with dry mouth [ 23 ].…”
Section: Introductionmentioning
confidence: 99%